Convalescent plasma therapy for COVID-19 – Donor selection strategies and establishment of a plasma bank - Mikael Kajova; Tamim Khawaja; Iris Levonen; Jukka-Pekka Pietilä; Jenni Virtanen; Sari H. Pakkanen; Hanna Välimaa; Arttu Nousiainen; Jussi Hepojoki; Tarja Sironen; Antti Vierikko; Jarkko Ihalainen; et al. (New Microbes and New Infections)
Background: Early in the COVID-19 pandemic, convalescent plasma (CP) emerged as a potentially effective treatment neutralising SARS-CoV-2. Early CP therapy with high neutralising antibody (NAb) titre may benefit COVID-19 outpatients and, in sufficient quantities even some hospitalised patients. This study details the process of setting up a CP bank, containing high- and low-titre CP for a clinical trial. Study design and methods: We identified 18–65-year-old convalescents with SARS-CoV-2 NAb titres of ≥1:40 in microneutralisation test (MNT). Following eligibility pre-screening, the Finnish Red Cross Blood Service (FRCBS) determined suitability as CP donors. Results: Of the 6466 COVID-19 convalescents contacted, 1481 provided serum, with 851 (57.5 %) exhibiting NAb titres ≥1:40. Participation barriers included reluctance, advanced age and, for women, insufficient body size. Of the volunteers, 125 were evaluated at FRCBS, with major exclusions for HLA antibodies (42 women), interferon antibodies (five men), and NAb titres waning below 1:20 (16 participants). Finally, 70 underwent plasmapheresis, resulting in 50 suitable CP donors (0.8 % of initial contacts and 3.4 % of those tested for NAb). Discussion: The process of setting up a CP bank proved challenging. Excessive laboratory workloads during a pandemic hamper their ability to conduct MNT, underscoring the need for rapid screening tests. Only a small proportion of our convalescents exhibited high-titre CP, this fraction declining over time because of waning immunity. Strict plasmapheresis criteria further constrained donor eligibility. Establishing a plasma bank requires meticulous planning to maximize efficiency. Detailed insights from current experiences may prove critical in future pandemics before other remedies and vaccines become available.